Weaving the Net: Making a Smart City Through Data Workers in Shenzhen. Issue 4 (2nd October 2022) - Zhao, Hailing; Douglas-Jones, Rachel
Abstract: This article focuses on data workers in Shenzhen, who, since 2013, have been recruited to fill positions in the city's Weaving the Net program (zhiwang gongcheng, 織網工程). The program, furthering both the expansion of city gridding management techniques and local experiments with China's Social Credit system, is designed to generate a daily set of data to inform the city's "Smart Brain", and is a core way of managing the city's "floating population". In this article, we approach the grid management of Shenzhen and its connection with histories of Chinese social control through data workers themselves. We argue that data workers expand our understanding both the integration of human-technological assemblages into smart city initiatives and the labor of data generation for programs of state social control. Extending STS approaches to smart city infrastructure, we use the figure of the data worker to the present both familiar and distinctive characteristics of Chinese Smart City initiatives.